HUBUNGAN KUALITAS PEMASOK BAJA TULANGAN TERHADAP KEPUASAN PELANGGAN - Fabiola Khasana; Bambang E. Yuwono; Dewi Rintawati (President University, 2017)
Customer satisfaction is a customer perception that expectations have been fulfilled by material and material suppliers. Customer satisfaction can be achieved if a construction product or service meets customer expectations. So almost every material and material suppliers now realize the importance of customer meaning for the company and strive to provide satisfaction to customers. The existing problem is what sub criteria can be used to measure supplier quality, customer satisfaction, and how the relationship between supplier quality and customer satisfaction. The purpose of this research is to know the sub criterion of supplier quality, customer satisfaction, and analyze the variable of supplier quality which is most dominant to customer satisfaction. Analyzed using Structural Equation Modeling (SEM) method. The results of this method are: the most dominant sub-quality suppliers criteria, namely Overcoming difficulties immediately and accurately, Providing good service from start to finish, Fast and timely service process, Physical quality of reinforcing steel meets Indonesian Industrial Standard and SNI, Price which is given is the price in accordance with the quality, Provides ease in contacting the company, and good employee competence. The most dominant customer sub-criterion is Overall supplier satisfies customer, Customer says positive, Customer recommends to others, Customer buys reinforcing steel in the same place, Customer seldom makes the switch, Makes the supplier the first choice for customer, Makes supplier as the best company in Indonesia, Meet customer expectation, Customers happy stock of goods from supplier, and promising product quality, Criteria of supplier quality relationship with the most dominant customer satisfaction, that is Empathy, Loyalty, Satisfaction, Responsiveness, Assurance From Supplier